Elastic wave energy scattering and propagation in composite structures - Aimakov, Nurkanat (2021)
This thesis considers the problem of high-frequency wave energy scattering and propagation in composite structures. In particular, structures made of the two-dimensional plate- or shell-like elements with composite laminate material are of interest. We propose an extension of the Dynamical Energy Analysis (DEA) method for such structures. For this purpose, we develop a semi-analytical and a hybrid Finite Element (FE) and Wave and Finite Element (WFE) methods to compute wave energy reflection/transmission at junctions of arbitrarily layered composite plates.